THE UTILIZATION OF WHEAT HULL ASH FOR THE PRODUCTION OF BARIUM AND CALCIUM SILICATES - Terzioglu, P.; Yucel, S.; Ozcimen, D. (PLAPIQUI(UNS-CONICET), 2013)
Wheat is the world's second most produced grain because of its high consumption rate, easy growth, multipurpose use and important role in the human diet. Every year, abundant amounts of wheat hull are obtained after shell process of the wheat as a waste material. Wheat hull, a by-product of the food industry, has low economic value. The utilization of wheat hull ash in various areas of industry can contribute to both financial and waste management strategies. In the present study, wheat hull ash that contains a high proportion of silica (43.22%), was utilized for barium and calcium silicate production. The wheat hull ash based barium and calcium silicate had a BET surface area of 30 and 54 m(2)/g, respectively. There has been no research on barium and calcium silicate production from wheat hull. So, this study will present originality on this area.
Keywords: Agricultural waste; barium silicate; calcium silicate; silica; wheat hull ash; RICE HUSK; PERFORMANCE; Engineering